Viral Oncogenesis Biomarkers in Diagnostics: From Tumor Viruses to Precision Cancer Medicine - Abrar, Areeba; Huma, Tamseel; Javaid, Areeba; Jabeen, Namra; Allah Rakha; Nadeem, Nimra; Shahid, Sarah (Indus Journal of Bioscience Research, 2025)
This comprehensive exploration delves into the intricate realm of oncogenic viruses, spanning the Epstein-Barr virus, Hepatitis B virus, Hepatitis C virus, Kaposi’s sarcoma herpesvirus, and Human T-cell lymphotropic virus type 1. An in-depth examination of specific components, including the functions of TAX and HPZ in HTLV-1, sheds light on the sophisticated mechanisms governing viral-induced oncogenesis. The discourse extends to the Human Papillomavirus, encompassing both Alpha and Beta types, elucidating their distinct roles in cancer pathogenesis. Transitioning to biomarkers, the discourse investigates microRNAs as potential diagnostic indicators in EBV-associated diseases. Serum biomarkers indicative of hepatocyte carcinoma resulting from HBV and HCV infections are scrutinized, highlighting the crucial role of biomarkers in early detection and prognosis. Tumor biomarkers and their implications in cancer diagnosis within the context of KSHV are explored. The discourse concludes with a focus on biomarkers in cervical cancer prevention linked to HPV, emphasizing their significance in screening and monitoring protocols.